الإنعزالية ودعوى الخصوصية في الديانة اليهودية / إعداد، رضوان عبدالجبار التايدي - تايدي، رضوان عبد الجبار (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
This thesis attempts to explore two main characteristics of Jewish identity namely; isolation and claim of specificity. These two vital foundations indeed portray a vivid mark of Jewish character along the history. Authoritative sources related to Judaism were consulted in order to provide fair and objective treatment of the topic. In order to comprehend these characteristics in details, attention was given to the factors underpinning such claims among Jewish community. Attention was along given to investigate the impact of Jewish isolation in economics and social realm. As far as the Jewish claim of specificity is concerned, the study also accentuates on the consequences of such claim Jewish life. The study in final attempts to compare these characteristics with other religions such as Islam and Christianity. The study discovered that the main factors stimulate Jewish isolation and specificity can be discerned throughout their sacred texts itself where encouragement, persuasion and support to these characteristics and the importance of Jewish people to be abided by these features were obviously mentioned. The study also found that Jewish isolation has a far reaching impact on economics and social realm in which the impact itself is not only confined to the race per se but to the world at large. By reinvigorating the concept of specificity the study found that it has significant consequences on Jewish life i.e. Jewish community elevate themselves as a pure and unadulterated race, proclaim themselves as God's chosen people and reinforce their legitimate right to return to 'their proclaimed land' Palestine and possess it.